Implement Explicite Instruction for Building Innovative Vocational Student Discipline and Culture - Widarto Widarto (Universitas Sarjanawiyata Tamansiswa, 2019)
Abstracts. The results of Widarto's research, Putut H., Prihatno K., (2018) show that the score of work discipline culture and innovative culture in the implementation of learning of industrial work culture in Diploma – III Mechanical Engineering students is still low. Each scored 2.78 and 2.67 on a scale of 4. The current study aims to: (1) Build a culture of work discipline and innovative culture in Diploma – III students of Mechanical Engineering through the implementation of the Explicite Instruction learning model; (2) Measuring the effectiveness of the Explicite Instruction learning model in enhancing the work culture of innovative aspects and the culture of work discipline in Diploma – III students of Mechanical Engineering, Faculty of Engineering, Yogyakarta State University. The method used is classroom action research (CAR). The subject of the study was 15 Diploma – III students of Mechanical Engineering. This class action research design consists of four stages of each cycle, namely planning, action, observation, and reflection. The results showed that: (1) Implementation of Explicite Instruction went well as expected and can be said to be successful because it reached the targets set as success criteria. The optimal implementation of Instruction requires 3 to 4 cycles; (2) Explicite Instruction is effective in enhancing student culture and innovative culture. This can be seen from the increase in the average score of discipline culture in each cycle in a row: 2.85; 2.98; 3.53; 3.67 and an increase in the average score of innovative culture each cycle in a row: 2.71; 2.84; 3.29; 3.42.